2018
DOI: 10.1182/blood-2017-08-801944
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Toll-like receptor 2 results in accelerated leukemogenesis in the NUP98-HOXD13 mouse model of MDS

Abstract: Myelodysplastic syndromes (MDSs) are hematopoietic stem cell disorders characterized by ineffective hematopoiesis and high rates of leukemic transformation. The only curative treatment is stem cell transplantation; therefore, new therapies are needed. 1 Recent studies suggest that enhanced Toll-like receptor (TLR) signaling may contribute to the pathogenesis of MDS. 2-10 Specifically, the expression of TLR2 is markedly elevated in the CD34 1 cells of MDS patients compared with healthy controls, 3,11 and TLR2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…5 Somewhat unexpectedly, a recent study suggests that TLR2 signaling has a protective role against leukemic transformation in a mouse model of MDS. 37 Mice expressing NUP98-HOXD13 (NHD13 mice) developed leukemia more rapidly when crossed with Tlr2-or MyD88-deficient mice. In the NHD13 model, TLR2 appears to be important for the MDS phase of the disease, but its loss may accelerate transformation to acute myeloid leukemia (AML).…”
Section: Functional Evidence Of Innate Immune Signaling Dysregulationmentioning
confidence: 99%
“…5 Somewhat unexpectedly, a recent study suggests that TLR2 signaling has a protective role against leukemic transformation in a mouse model of MDS. 37 Mice expressing NUP98-HOXD13 (NHD13 mice) developed leukemia more rapidly when crossed with Tlr2-or MyD88-deficient mice. In the NHD13 model, TLR2 appears to be important for the MDS phase of the disease, but its loss may accelerate transformation to acute myeloid leukemia (AML).…”
Section: Functional Evidence Of Innate Immune Signaling Dysregulationmentioning
confidence: 99%
“…However, co-transduction of an activated NUP98-HOXD13 fusion gene and MN1 alone is able to induce AML in engrafted mice [165]. More recently, it has been demonstrated that the loss of Toll-like receptor 2 too is able to accelerate leukemic progression in NUP98-HOXD13 mouse model [166]. During leukemic progression, the presence of the fusion transcript NUP98-HOXD13 is associated with other hematopoietic disorders, such as myelodysplastic syndrome (MDS), chronic myeloid leukemia and blast crisis.…”
Section: Hoxd13mentioning
confidence: 99%
“…We previously reported that young adult NHD13 mice have increased surface TLR2 on their hematopoietic stem and progenitor (c-Kit+Sca-1+Lineage- [KSL]) cells compared with WT littermates [ 19 ]. Using flow cytometry, we determined that surface expression of the TLR2 binding partners, TLR1 and TLR6, is also increased on KSL cells of the NHD13 mice compared with WT littermates ( Figure 1A , B ; Supplementary Figure E1 , online only, available at www.exphem.org ).…”
Section: Resultsmentioning
confidence: 99%
“…This well-characterized transgenic MDS model expresses the NUP98-HOXD13 fusion from the hematopoietic Vav-1 promoter and exhibits many of the salient features of human MDS including cytopenias, bone marrow dysplasia, and transformation to acute leukemia [ 18 ]. Notably, the HSPCs of the NHD13 mice, like those of humans with MDS, have increased expression of TLR2, and we recently reported that complete loss of TLR2 or the TLR signaling adaptor MyD88 is associated with earlier leukemic transformation in the NHD13 mice [ 19 ]. Mechanistic studies revealed that loss of TLR2 resulted in a reduction of activated caspase-1 and lower rates of cell death in preleukemic HSPCs [ 19 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation